The AI Chasers. - Tucker, Patrick (Futurist)
The advent of a human-level artificial intelligence, a machine capable of the richness of expression and subtlety of thought associated with humanity, promises to generate huge wealth for those who develop it. According to the Business Communications Company, the market for artificial intelligence software and products hit $21 billion in 2007, a remarkable figure that does not touch on the wealth that a human-level artificial intelligence could earn across industries. After over 50 years of research, however, scientists have yet to create an artificial general intelligence (AGI). The writer discusses the fact that intellectuals and researchers at the forefront of the field differ over how soon AGI might arrive and what it might mean for humanity.